(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes problems, tasks and results in the field of public education in Khorezm region during the years of independence. The article provides information of the achievements of teachers and students working in public education, in international competitions, as well as the shortcomings and problems in the field of public education.